2014
DOI: 10.1111/acer.12456
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroloquinoline Quinone-Secreting ProbioticEscherichia coliNissle 1917 Ameliorates Ethanol-Induced Oxidative Damage and Hyperlipidemia in Rats

Abstract: Accumulated PQQ in tissues prevents hepatic and systemic oxidative damage. PQQ along with SCFAs reduced hyperlipidemia, which can be correlated with changes in mRNA expression of hepatic lipid metabolizing genes. Our study suggests that endogenous generation of PQQ by EcN could be an effective strategy in preventing alcoholic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Engineered PQQsecreting E. coli str. Nissle protected against hepatic hyperlipidaemia in a rat model of ethanolinduced liver damage 229 , supporting PQQ as a potential novel strategy to reduce risk of NAFLD development. The key to optimizing probiotic or prebiotic approaches are functional maps of both healthy and obese gut microbiota, particularly for infants, which are only just being investigated 230 .…”
Section: Targeting the Gut–liver Axismentioning
confidence: 84%
“…Engineered PQQsecreting E. coli str. Nissle protected against hepatic hyperlipidaemia in a rat model of ethanolinduced liver damage 229 , supporting PQQ as a potential novel strategy to reduce risk of NAFLD development. The key to optimizing probiotic or prebiotic approaches are functional maps of both healthy and obese gut microbiota, particularly for infants, which are only just being investigated 230 .…”
Section: Targeting the Gut–liver Axismentioning
confidence: 84%
“…With the development of modern intensive farming, chickens are prone to oxidative stress (Salami, Majoka, Saha, Garber, & Gabarrou, ). Numerous studies found that dietary probiotics in diets were beneficial in oxidation resistance, scavenging ROS and promoting antioxidant capability (Chen, Gong, & Xu, ; Singh, Pandey, & Naresh, ). Antioxidant enzymes (SOD, CAT, GSH and GSH‐Px) serve as the first line to suppress the oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences suggest that PQQ can permeate to subcellular organelles such as mitochondria (Stites et al, 2006). In the present study 3.7 kb pqqABCDE gene cluster from G. oxydans 621H was used to reduce the plasmid load in contrast to our earlier reports of 13.3 kb pqq gene cluster from Pseudomonas fluorescens B16 Singh et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…PQQ was extracted from the bacterial strains as described by Suzuki et al (1990) and used by Singh et al (2014). Faeces and liver homogenate were collected for PQQ estimations from rat gut lumen and liver tissues, respectively.…”
Section: Pqq Extraction and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation